Development of a consensus-based core outcome set for post-treatment recovery in adults with epilepsy and comorbid depression or anxiety: A Delphi and ICF-guided protocol - Yan Wang; Zaibang Feng; Zhiyue Guo; Hongxia Xing; Zhaohong Guo; Xinli Zhao; Zubing Mei (PLoS ONE, 2025)
Introduction Up to 50% of adult patients with epilepsy experience comorbid depression or anxiety, complicating post-treatment recovery and requiring tailored outcome assessment. No core outcome set (COS) exists for this dual-diagnosis population, unlike broader epilepsy COSs or quality-of-life COSs for drug-resistant epilepsy, which do not prioritize mental health comorbidities. This protocol outlines the development of a standardized COS to evaluate post-treatment recovery in adults with epilepsy and comorbid depression or anxiety, using the International Classification of Functioning, Disability, and Health (ICF) framework to ensure a biopsychosocial perspective. This COS aims to enhance cross-study comparability and inform personalized care for this underserved group. Methods and analysis This study will employ a three-phase process: (1) A systematic review of outcomes in epilepsy with comorbid depression or anxiety in adult patients, searching PubMed, Embase, and Cochrane Library per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including outcomes such as seizure control, mood stability, cognitive function, social reintegration, and suicide-related outcomes; (2) Mapping outcomes to ICF domains (body functions, activities, participation) for comprehensive coverage; and (3) A three-round Delphi survey using a 9-point Likert scale to achieve consensus among an international panel of ≥60 stakeholders, including neurologists, psychiatrists, psychologists, patients, and caregivers, with ≥20% from low- and middle-income countries. Consensus requires ≥70% agreement on scores of 7–9 (critically important) and ≤15% on 1–3 (low importance). The COS will capture domains like seizure control, mood stability, cognitive function, and social reintegration. Discussion This COS will address a critical gap by standardizing outcome measurement for adults with epilepsy and mental health comorbidities, complementing broader COSs, such as the Epilepsy Outcome Set for Effectiveness Trials (EPSET), by focusing on mental health recovery, including suicide-related outcomes, and extending quality-of-life-focused sets, such as those using the Quality of Life in Epilepsy (QOLIE) scales, to include neurological and functional outcomes. The ICF-guided, patient-inclusive approach ensures global relevance. Potential limitations, including stakeholder bias, will be mitigated through diverse recruitment and robust consensus methods. Conclusion This protocol leverages Delphi methodology and ICF principles to develop a novel COS for a complex dual-diagnosis population. By prioritizing mental health recovery in adults, including critical outcomes like suicide prevention, it offers a distinct tool to enhance research and clinical practice, with future validation planned to ensure applicability across settings. PROSPERO registration number CRD42024576141